Implementation of a Tracker-Assisted Modeling Activity in an Online Advanced Physics Experiment Course - Pratidhina, Elisabeth; Rosana, Dadan; Kuswanto, Heru (Journal of Education and e-Learning Research, 2021)
Experiment or laboratory work is an essential part of physics and other science courses. However, due to the COVID-19 pandemic, face-to-face classes have had to be transformed into remote classes. Because laboratory access has become very limited, technology must be utilized to substitute for hands-on activity in laboratory-based courses. Additionally, maintaining students’ motivation during remote classes is also challenging. In this paper, we report on the implementation of modeling activities using Tracker in our online Advanced Physics Experiment course. We examine the effectiveness of Tracker-assisted modeling activity in improving students’ graph interpretation skills on the topic of Fraunhofer-Diffraction. The results show that 20 out of 21 participants demonstrated an increase in graph interpretation skills. The average normalized gain is 0.74, which can be seen as a high degree of improvement. Although the activity did not allow students to practice hands-on skills, this activity can encourage students to practice other science-related skills. Moreover, according to the survey, students feel more motivated to learn physics online after being exposed to the modeling activity.